Religion in the European Refugee Crisis (Religion and Global Migrations, 2018)
This book explores the roles of religion in the current refugee crisis of Europe. Combining sociological, philosophical, and theological accounts of this crisis, renowned scholars from across Europe examine how religion has been employed to call either for eliminating or for enforcing the walls around "Fortress Europe." Religion, they argue, is radically ambiguous, simultaneously causing social conflict and social cohesion in times of turmoil. Charting the constellations, the conflicts, and the consequences of the current refugee crisis, this book thus answers the need for succinct but sustained accounts of the intersections of religion and migration.